Changing agricultural scenario and its impact on food habit in north east states of India - Mandal, Ram Krishna (Food Biology, 2011)
<span style="font-size: 14pt; font-family: ";Times New Roman";,";serif";; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In spite of the population explosion, it is possible to substantially augment the carrying capacity of the land, doubled or even tripled the food grain production and achieved rapid industrialization to provide economic security and improve the quality of life of theÃ‚Â people of North East States of India. Since the planning period starts, stress has always been laid on the production of food grains to meet the requirements of the increased population. In this respect, Ã‚Â North Eastern Region of India Ã‚Â can not be compared with all other states of Indian Federation as growth of population is most alarming in this region due to immigration from neighbouring border countries and the flow of population to this region from other states of Indian Union. This problem of food insecurity can be linked with the backwardness in agricultural development